2018
DOI: 10.2319/103117-737.1
|View full text |Cite
|
Sign up to set email alerts
|

Extraversion and openness to experience moderate the relationship between orthodontic treatment need and oral health-related quality of life in adolescents:

Abstract: The relationship between orthodontic treatment need and quality of life is moderated by personality traits. Early adolescents with higher extraversion and openness to experience are less affected by increased orthodontic treatment need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
3
5
0
Order By: Relevance
“…In addition, conscientiousness could be associated with more commitment, organization, and reporting changes in oral status and oral health related impacts. This agrees with the findings of previous studies that linked personality traits with oral health related quality of life that associated other types of orthodontic treatment 2, [41][42][43][44][45][46] . Higher scores of extraversion and openness Table 6.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, conscientiousness could be associated with more commitment, organization, and reporting changes in oral status and oral health related impacts. This agrees with the findings of previous studies that linked personality traits with oral health related quality of life that associated other types of orthodontic treatment 2, [41][42][43][44][45][46] . Higher scores of extraversion and openness Table 6.…”
Section: Discussionsupporting
confidence: 92%
“…Unstand www.nature.com/scientificreports/ personality traits were accompanied with less impact of orthodontic treatment needs on oral health related quality of life 42 . Also, less satisfaction and more negative impacts after orthodontic treatment were associated with higher levels of neuroticism 2 .…”
Section: Dependent Variable Predictorsmentioning
confidence: 99%
“…His finding showed that adolescents with higher extraversion and openness to experience are less affected by increased orthodontic treatment need. [24]…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to investigate the potential role of personality traits as mediators or moderators of the association between clinically assessed treatment need and the psychosocial impact of dental aesthetics (PIDA) in adolescents and adults. Based on previous reports, 10,22 we hypothesised that personality traits would not moderate the association between malocclusion and PIDA in adults, and that extraversion and openness would have a protective moderating effect on this association in adolescents.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous instruments are used for self‐reporting of OHRQoL. The Oral Health Impact Profile (OHIP) 7,8 and Child Perceptions Questionnaire (CPQ) 9,10 are generic tools that measure overall oral health across different dimensions, such as oral symptoms (pain, gingivitis and bad breath); functional limitations; handicap; social disability; and emotional problems. In their study of university students, Klages et al 11 reported an adaptation of the Orthognathic Quality of Life Questionnaire 12 that excluded the function scale and included a new scale, that is, dental self‐confidence (DSC).…”
Section: Introductionmentioning
confidence: 99%